Primary and Secondary School Teachers’ Perception of the Assessment of Historical Knowledge and Skills Based on Classroom Activities and Exercises - Trigueros-Cano, Francisco Javier; Molina-Saorín, Jesús; López-García, Alejandro; Álvarez-Martínez-Iglesias, José María (Frontiers in Education, 2022)
The aim of this paper is to identify the most suitable activities and exercises for the development of historical knowledge and skills and their subsequent evaluation. On this basis, a quantitative study has been carried out among primary and secondary school teachers in several Spanish regions in which their perception of what types of exercises and activities (of those proposed in their History or Social Science classes) are most suitable for assessing the historical knowledge and skills that students are expected to acquire has been extracted. The results show that exercises involving the interpretation of texts and images which require students to think about and apply the historical knowledge acquired are very useful, as are questions which seek historical explanation and causal reasoning; however, objective tests (multiple-choice tests, linking dates with events, etc.) or short questions about historical events or characters are not considered to be very suitable for the adequate development of historical knowledge and, therefore, of historical competences.